An injectable platelet lysate-hyaluronic acid hydrogel supports cellular activities and induces chondrogenesis of encapsulated mesenchymal stem cells. (1st January 2019) - Jooybar, Elaheh; Abdekhodaie, Mohammad J.; Alvi, Mansour; Mousavi, Abbas; Karperien, Marcel; Dijkstra, Pieter J.
Graphical abstract: Abstract: Developing scaffolds that can provide cells and biological cues simultaneously in the defect site is of interest in tissue engineering field. In this study, platelet lysate (PL) as an autologous and inexpensive source of growth factors was incorporated into a cell-laden injectable hyaluronic acid-tyramine (HA-TA) hydrogel. Subsequently, the effect of platelet lysate on cell attachment, viability and differentiation of human mesenchymal stem cell (hMSCs) toward chondrocytes was investigated. HA-TA conjugates having a degree of substitution of 20 TA moieties per 100 disaccharide units were prepared and crosslinked in the presence of horseradish peroxidase and low concentrations of hydrogen peroxide. The storage moduli of the gels ranged from 500 to 2000 Pa and increased with increasing polymer concentration. In contrast to a retained round shape of the cells when using pure HA-TA hydrogel, the hMSCs attached and spread out in PL enriched matrix. The enrichment of hMSCs laden HA-TA hydrogels with PL induced a cartilage like extra cellular matrix deposition in vitro. The hMSCs increasingly deposited collagen type II and proteoglycans over time. The deposition of the new extracellular matrix (ECM) is simultaneous with gel degradation and resulted ultimately in the formation of a tough dense matrix. These findings demonstrate the potential of injectable HA-TA-PL hydrogel as a cell delivery system for cartilage regeneration. Statement of Significance: Cartilage tissue has limited ability to self-repair because of its avascular nature. To have an efficient cartilage tissue regeneration, we combined platelet lysate (PL), as an autologous and inexpensive source of growth factors, with an injectable hyaluronic acid tyramine (HA-TA) hydrogel scaffold. Platelet lysate had a vital role in supporting human mesenchymal stem cells (hMSCs) activities, like cell attachment, viability and proliferation in the 3D hydrogel structure. Also, the hMSCs encapsulated HA-TA induced hyaline cartilage generation when placed in chondrogenic differentiation medium. This study introduces a new system for cartilage tissue engineering, which can be injected in a minimally invasive manner and is rich with patient's own growth factors and biological cues.